The Effect of TGT Cooperative Learning Model Assisted by Multimedia Learning on Cooperation and Learning Outcomes of Class V Elementary School Students for Social Sciences - Ulil Azmi Banani; Aman Aman (STAI Hubbulwathan Duri, 2022)
The purpose of this study was to determine the effect of the Cooperative Learning Model Type Team Games Tournament (TGT) Assisted by Multimedia Learning on Cooperation and Learning Outcomes of Fifth Grade Elementary School Students in Social Sciences. The design in this study is a quasi-experimental with one group pre-test post-test. The purpose of using this design is to determine whether or not there is an increase in the application of the cooperative learning model of the type of TGT assisted by multimedia learning on the cooperation and learning outcomes of fifth grade elementary school students in social studies subjects. The subjects in this study were the fifth grade elementary school students totaling 30 students. The research instrument consisted of observation sheets and questionnaires to measure cooperation and student learning outcomes. Based on the research that has been done, it is found that cooperative learning of the type of TGT assisted multimedia learning has an influence on cooperation. It was also found that cooperative learning of the type of TGT assisted by multimedia learning had an influence on student learning outcomes. So it is necessary to increase cooperative learning type TGT to improve cooperation and student learning outcomes.